PENGARUH FRAUD HEXAGON TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI - Sri Wulandari; Sasmita Nabila Syahrir; Surianto Ilham; Hasmawati Timpa (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the effect of Fraud Hexagon on Financial Statement Fraud in mining companies listed on the Indonesia Stock Exchange (IDX). Fraud Hexagon consists of pressure, opportunity, rationalization, capability, arrogance, and collusion, while Financial Statement Fraud is measured using the Beneish M-Score. This study uses a quantitative approach with logistic regression analysis and purposive sampling techniques based on the companies' financial statements and annual reports for the observation period. The results show that simultaneously, the Fraud Hexagon influences Financial Statement Fraud, but partially, not all variables have a significant influence. These findings are expected to contribute to the detection and prevention of financial statement fraud in the mining secto. Keyword: Fraud Hexagon, Financial Statement Fraud, Beneish M-Score, Pertambangan.